Static and Dynamic Process Change - Wei Song; Jacobsen, Hans-Arno (IEEE transactions on services computing, 2018)
Approaches for modifying processes both at build time and at run time are commonly referred to as process change, which play an increasingly important role in the enterprise today, where more than ever before, changing requirements must be rapidly accommodated. Over the years, approaches for supporting process change have received much attention from the research community. In spite of that, no comprehensive survey of this important subject exits. To draw a clear picture that analyzes the status of research in this area, in this paper, we conduct a systematic literature review on process change. The resulting survey sheds light on how to classify approaches for process change, determines what the principal research questions and challenges are, and identifies several research directions for further study.